Pengaruh Social Media Marketing Dan Electronic Word Of Mouth (e-Wom) Terhadap Keputusan Pembelian Pada Toko Lemper Purnama Cabang Fatmawati Jakarta Selatan - Listianto Adi Prasetio; Nani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of Social Media Marketing (SMM) and Electronic Word of Mouth (e-WOM) on purchasing decisions at Lemper Purnama Store, Fatmawati Branch, South Jakarta. The research sample was taken from Lemper Purnama Store consumers using a survey method with an online questionnaire. The research data includes sales data, the use of digital platforms (Instagram, WhatsApp Business, GoFood, and GrabFood), as well as a pre-survey of e-WOM. The results show that Social Media Marketing has a significant effect on purchasing decisions, indicated by a significance value of 0.000<0.050.000 < 0.050.000<0.05 and a calculated t-value of 6.641>1.9846.641 > 1.9846.641>1.984. Similarly, Electronic Word of Mouth (e-WOM) also has a significant effect on purchasing decisions, shown by a significance value of 0.000<0.050.000 < 0.050.000<0.05 and a calculated t-value of 20.784>1.98420.784 > 1.98420.784>1.984. Furthermore, simultaneously, Social Media Marketing and Electronic Word of Mouth (e-WOM) have a positive and significant influence on purchasing decisions, as evidenced by the F-test, where the calculated F-value is 431.965>3.09431.965 > 3.09431.965>3.09 and the significance value is 0.000<0.050.000 < 0.050.000<0.05. These findings confirm that the regression model can be used to predict purchasing decisions.